Pelaksanaan Pendidikan Keterampilan Otomotif di Panti Sosial Bina Remaja Indralaya Kabupaten Ogan Ilir - Supriadi, Isen; Hakim, Imron A.; Waty, Evy Ratna Kartika (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2020)
This study aims to skill to understand the implementation of the education automotive academic year 2019 / 2018 provided by social institution youth kabupaten indralaya ogan an ilir.Type used the quantitative research descriptive.Population were 14 people and entire population object sample taken to be research.Data collection method used in this research was survey methods, and observation.Research show that the implementation of education skill automotive seen from ten members, indicators learning instructors learning, of learning, learning methods, learning facilities, place learning, funds, learning study groups, a learning program and study results good criteria. they came from ten indicators it is still for facilities there is a shortage of learning that is a machine tool motor still less like a piston , a weaver shuttle ring , the crank shaft , and the not institution based on the learn to an apprentice dibengkel automotive in a society.